Methods for streamlining intervention fidelity checklists: An example from the Chronic Disease Self-Management Program - SangNam eAhn; SangNam eAhn; Matthew Lee eSmith; Mary eAltpeter; Basia eBelza; Lindsey ePost; Marcia Gail Ory (Frontiers Media S.A., 2015)
*